Vaccination issues in patients with chronic kidney disease. (February 2014) - Mathew, Roy; Mason, Darius; Kennedy, Jeffrey S
<x xml:space="preserve">Abstract</x> Infections are an important cause of morbidity and mortality among patients at all stages of chronic kidney disease. Prevention through vaccination remains the best strategy to minimize the adverse consequences associated with these infectious diseases in this, and all, populations. Unfortunately, patients with chronic kidney disease demonstrate inadequacies of specific immune-cell function that are required for generating a protective vaccine response. Nevertheless, early vaccination of this high-risk population has demonstrated good clinical outcomes during progression to late-stage disease. We review the available evidence linking immune impairment in adult patients with late-stage chronic kidney disease to diminished vaccine responses. We highlight the importance of early vaccination in disease with high risk for development of CKD and novel vaccine approaches in development that may help to address improvement in protective boosting of immunity during late-stage disease.